Pembinaan instrumen amalan pentaksiran guru matematik sekolah menengah - Abdullah Mohd Faizal Nizam Lee, Hamzah Mohd Sahandri Gani, Che Ahmad Che Nidzam, Adnan Mazlini, Mohamed Noh Noraini, Suhaimi Shafini, (N/A, 2014)
Pembinaan instrumen amalan pentaksiran guru matematik sekolah menengah by Abdullah Mohd Faizal Nizam Lee, Hamzah Mohd Sahandri Gani, Che Ahmad Che Nidzam, Adnan Mazlini, Mohamed Noh Noraini, Suhaimi Shafini,